Pengaruh Attitude Toward Behavior, Perceived Behavioral Control, dan Subjective Norm terhadap Entrepreneurial Intention Mahasiswa Non-Ekonomi - Anggraini, Rona Desi Sanchez; Patricia, Patricia (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
Entrepreneurship in Indonesia has been developing rapidly these past years. A survey among 210 university students without economic or business educational background showed that they also have an intention to be an entrepreneur and that their major in the university is not a barrier for them to start their own business. This study uses three independent variables which are attitude toward behavior, perceived behavioral control, and subjective norms to see the impact towards students’ entrepreneurial intention. Data was processed using PLS-SEM (Partial Least Square – Structural Equation Modeling). The finding of this study showed that attitude toward behavior, perceived behavioral control, and subjective norms have a significant impact towards students’ entrepreneurial intention. This study can be used by the government and universities to create programs that will increase the entrepreneurial spirit among students from various educational background and open opportunities for them to participate in entrepreneurial activities.